Overview of Agile frameworks in Computer Science education - Pavlo V. Zahorodko (Освітній вимір, 2023)
This paper explores the application of Agile frameworks in education to enhance the learning process. The lack of a generalized approach to Agile in education prompted an analysis and comparison of various frameworks, including Scrum, eduScrum, Agile Learning Loops (ALL), and other Scrum-based approaches. The Agile Manifesto was also reinterpreted for educational settings. The review highlights the differences and similarities among these frameworks in terms of their suitability for education, support for classic increments, project-based approach, documentation, technological stack, and role distribution. The analysis concludes that while Agile is increasingly used in education, there is no standardized methodology. The reviewed frameworks offer valuable insights, but their implementation requires experimentation and adaptation to individual educational contexts.